Controllable Synthesis and Ostwald Ripening of Silver Nanoparticles - Zhang, Wanzhong; Qiao, Xueliang; Qiu, Xiaolin; Chen, Qingyuan; Cai, Yuchun; Chen, Haiqiang (Current Nanoscience, 2013)
Silver nanocrystals with different particle sizes were prepared by chemical reduction of silver nitrate with sodium borohydride in the presence of citrate. The formation and ripening mechanisms of silver nanocrystals were also proposed. TEM images show that the mean diameter of silver nanocrystals is about 2 nm by addition of NaBH4 all at once and 10 nm by addition of NaBH4 drop by drop. UVVis spectra show that the mean diameter of the nanocrystals prepared at 0°C is smallest and then increases with the temperature. The aging time has obvious influence on the small nanocrystals and little influence on the big nanoparticles. Only the crystal planes of small nanocrystals have a high possibility of selective adsorption of citrate at the early stage of aging process. However, the smaller nanocrystals in the colloidal solution have aggregated into larger nanoparticles after 8 h of aging.
Keywords: Adsorption